Promotion of Nationalism through Caste: A Study of Rabindra Nath Tagore’s Gora - Kandel, Bhanu Bhakta Sharma (The Outlook: Journal of English Studies, 2021)
The original idea of caste system was engineering the society on the basis of labor division by providing every sector of society a distinct and important role to make the Hindu society an integrated whole making every group in the society depending on every other or the society was engineered to be completely inter-dependent, but the problem is that it has been misused as a means of social exploitation, oppression that has led the society towards mutual hatred and disintegration. The main objective of this research article is to find out how Gora, the protagonist of Rabindra Nath Tagore’s novel Gora, has used the idea of caste division as a means to promote nationalism among the people. Theoretical insights of liberal nationalism are used to analyze the primary text with the help of theoretical insights of Edward Soja’s ‘Thirdspace’. The article examines and analyzes how one can help strengthen social integration by respecting the others and offering the people justice even though difference is inevitable among the people living in a society. The article concludes that caste system can be exercised as a means of cultural nationalism by celebrating the difference among the people and respecting the jobs done by others.